Factors for Sustainable Return of Highly Qualified Bulgarians: Motivation and Professional Trajectories - Ivanova, Vanya (Research Papers, 2021)
The highly qualified migration is the desired migration all around the world in 21st century. Attracting back and retaining the highly qualified specialists becomes a policy for many countries with recent emigration history. The study explores the motivation factors and professional trajectories of young highly qualified Bulgarians who returned to Bulgaria in the years around 2010, comparing and analysing the answers of the interviewees conducted one to three years upon their return with their current situation 10 years later. The study is qualitative based on semi-structured interviews and its core value lies in its longitudinal character and the possibility to review the interviewees’ situation in a longer time span. The paper focusеs on: sustainability of the return: are the highly qualified returnees still in Bulgaria; professional realization: how their professional trajectories have developed through time; other factors of sustainable return: what keeps them in Bulgaria beside the professional realization and civil activism: to what extend returnees participate in different forms of civil initiatives. As main conclusions and factors for sustainable return stand out the development of the economy and the possibilities for innovations, the realization of new professional niches along with the social factors of taking care of own family and/or older parents/relatives.